Next generation magnetic field measurements from low-earth orbit satellites enable enhanced space weather operations - Le, Guan; Knipp, Delores J.; Rastätter, Lutz; Lu, Gang; Ozturk, Dogacan Su; Slavin, James A.; Maute, Astrid; Klenzing, Jeffrey; Zou, Shasha; Espley, Jared R.; Purucker, Michael; Akhavan-Tafti, Mojtaba; et al. (Frontiers in Astronomy and Space Sciences, 2022)
Large-scale current systems in the ionosphere and the mag¬netosphere are intimately controlled by the solar wind-magnetosphere interaction and the magnetosphere-ionosphere coupling. During space weather events, these currents reconfigure and intensify significantly in response to enhanced solar wind-magnetosphere interaction, facilitating explosive energy input from the magnetosphere into the ionosphere-thermosphere system and inducing electric current surges in electric power systems on the ground. Therefore, measurements of magnetic manifestations associated with the dynamic changes of the current systems are crucial for specifying the energy input into the ionosphere-thermosphere system, understanding energy dissipation mechanisms, and predicting the severity of their space weather impacts. We investigate the potential uses of high-quality magnetic field data for space weather operations and propose real-time data products from next generation constellation missions that enable improved space weather forecasting and mitigation.